Tongue lesions and anomalies in a sample of Yemeni dental patients: A cross-sectional study. - Mohammed Ali Al-Wesabi; Manal Al-Hajri; Anas Shamala; Saba Al-Sanaani (Universidad de Concepción., 2017)
Background: Tongue examination helps considerably in diagnosing the underlying health state of the patient, especially in the cases of chronic diseases. The aim of this study is to determine the prevalence and association of tongue lesions with risk factors among Yemeni dental patients. Materials and methods: An oral medicine specialist examined all 713 patients attending the dental polyclinics at the University of Sciences and Technology (Sana'a, Yemen). The examination sheet was designed to include information related to patient characteristics, medical history, dental history, habits, and tongue lesions. Results: The prevalence of tongue lesions among the examined participants was 76.5%. The prevalence rate was 83.4% for males and 69.2% for females. Fissured tongue was the most common condition. Logistic regression analysis indicated that older age (p<0.001), gender (p=0.007), khat chewing (p<0.001), and smoking (p=0.001) were associated with fissured tongue; gender (p<0.001), khat chewing (p<0.001), and smoking (p<0.001) were associated with hairy tongue; and older age (p<0.001), khat chewing (p=0.001), and smoking (p=.021) were associated with coated tongue. Conclusion: The prevalence of tongue lesions among this sample of Yemeni population was 76.5%; fissured tongue and hairy tongue were the most prevalent lesions. Khat chewing, smoking, and older age were the associated risk factors for many of studied lesions and anomalies.